Growth, Yield and Resistance Responses of Three Cultivars on True Seed Shallots to Twisted Disease with Salicylic Acid Application - Rachmanto Bambang Wijoyo; Endang Sulistyaningsih; Arif Wibowo (Universitas Sebelas Maret, 2020)
Twisted disease is one of the main diseases on shallot caused by Fusarium sp. One method to increase the resistance of shallot cultivars to the twisted disease can be performed by using True Seed Shallot (TSS) combining with a salicylic acid application. TSS is known as free pathogen. The objective of the research was to examine the effects of a salicylic acid application to the growth, yield and resistance responses of TSS on Tuktuk, Sanren and Lokananta cultivars to the twisted disease. The research was arranged in factorial Completely Randomized Design (CRD), consisting of two factors with three replications. The first factor included Tuktuk, Sanren and Lokananta cultivars and the second factor comprised salicylic acid applications (without salicylic acid and inoculation, without salicylic acid with inoculation, immersion treatment of salicylic acid with inoculation, spray treatment with inoculation as well as immersion and spray treatment with inoculation). The results showed that the application of salicylic acid in different treatments had the same effects on the growth, yield and resistance of TSS. An interesting result is found, in which the application of salicylic acid by immersing and spraying could reduce the incidence of twisted disease by 12.5% in TSS. Therefore, the application of salicylic acid by immersing and spraying can be one of the recommended twisted disease management.